Classic Content-Analysis and Text Analysis: Terminological and Methodological Differences - Ivanov, Oleg (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The paper is devoted to conceptual and methodological review of the method of content analysis in relation to the procedures and techniques of quantitative analysis of text data. The author provides definitions of the terms "methodology", "method", "procedure", "technique" in the context of study of texts in social sciences. The basic terminological field of correlation of "classic" content analysis, "text-mining", "computer content analysis" within the framework of qualitative and quantitative paradigms, "analysis of textual data", "analysis of natural language", "quantitative content analysis", "qualitative content analysis" and the theoretical and methodological background of their application are considered. The world experience of classification of methods of quantitative analysis of texts in social sciences and the existing contradictions between the various schools of content analysis are briefly presented. The necessity to update the requirements to the content analysis research in conditions of transition to the information society and use of computer technology in the study of communication is proved.